28.1k views
4 votes
Calculate the average rate of change of f(x) = 1 x - x2 - 2 for 3 ≤ x ≤ 6. A) -163 18 B) -18 163 C) 163 18 D) 18 163

2 Answers

2 votes
The answer is A.)-163/18
User Rieko
by
6.1k points
6 votes
To solve this we are going to use the average rate of change formula:
A(x)= (f(b)-f(a))/(b-a)
where

A(x) is the average rate of change of the function

f(a) is the position function evaluated at
a

f(b) is the position function evaluated at
b

a is the first point in the interval

b is the second point in the interval

We can infer for our problem that the first point is 3 and the second point is 6, so
a=3 and
b=6. Lets replace those values in our formula:

A(x)= (f(b)-f(a))/(b-a)

A(x)= (f(6)-f(3))/(6-3)

A(x)= (6-6^2-2-(3-3^2-2))/(3)

A(x)= (-32-(-8))/(3)

A(x)= (-32+8)/(3)

A(x)= (-24)/(3)

A(x)=-8

We can conclude that the average rate of change of the function f(x) = 1 x - x2 - 2 for 3 ≤ x ≤ 6 is -8
User Elyce
by
5.8k points